1988
DOI: 10.1111/j.1365-2222.1988.tb02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity and cross‐reactivity of cat and dog allergenic extracts

Abstract: This study aims to eonfirm that eat allergen I (CAT-1) is a major allergenic determinant in cat-sensitive patients, and to further define the role of other determinants, as well as to identify the determinants responsible for the cross-reactivity between cat and dog extracts. Firstly, the allergenic determinant with an electrophoretic mobility of 18 kD (corresponding to CAT-1) is indeed a major allergenic determinant being recognized by the majority (75%) of cat-sensitive subjects. Secondly, the cross-reactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Can f I is a polypeptide with a molecular weight of 22-25 kD. Albumin is another allergen of some importance, the molecule is considered responsible for cross reaction between cat and dog extracts [24]. Assays based on monoclonal or monospecific antibodies have shown Can f I levels to be one order of magnitude above those of Fel d I i.e.…”
Section: Dog Allergensmentioning
confidence: 99%
“…Can f I is a polypeptide with a molecular weight of 22-25 kD. Albumin is another allergen of some importance, the molecule is considered responsible for cross reaction between cat and dog extracts [24]. Assays based on monoclonal or monospecific antibodies have shown Can f I levels to be one order of magnitude above those of Fel d I i.e.…”
Section: Dog Allergensmentioning
confidence: 99%
“…Patients allergic to cats and dogs frequently display IgE reactivity against allergens from different animals (444,445). Albumins have been recognized as relevant crossreactive allergens (446).…”
Section: Other Mitesmentioning
confidence: 99%
“…Only one allergen, the 69-kDa albumin, is present in both species and is known as a cross-reactive allergen (table 12) [118]. Nevertheless, inhibition studies surprisingly showed cross-reactivity of cat and dog extracts under certain conditions [108,118,119,120]. Data demonstrated cross-reactivity for cat hair and dog hair but not for cat saliva and dog saliva or cat urine and dog urine, respectively [108].…”
Section: Allergen Extracts Derived From Vertebratesmentioning
confidence: 99%